Scenario analysis different paths spotify may take - Silva, Francisco Maria Koehler Monteiro Da (2020)
The report consists in the implementation of a scenario analysis to understand the different paths the world economy may take which might impact differently. First, a macroeconomic outlook was made in order to grasp recent events and their impact in the world. Then, it was identified US-China trade war as the main source of uncertainty in the world and two possible evolutions for this risk. The conclusion is that, in a negative scenario, Spotify’s expected price is $127andexpected return is -15.3%. In the positive scenario, Spotify’s expected price is $219 and expected return is45.7%.